ANALYSIS OF PRESSURE AND OPPORTUNITY FACTORS ON FRAUD OF FINANCIAL REPORTS IN MANUFACTURING COMPANY - Lulu Ainun; Harti Budi Yanti (EBID: Ekonomi Bisnis Digital, 2023)
Fraud is an act of an individual or a group of people that aims to generate personal or group benefits from the actions taken, including actions that can harm other individuals and business entities. The purpose of this study is to test, and provide empirical evidence about the effect of financial stability, external pressure, financial targets, and the effectiveness of oversight of fraudulent financial reporting. This type of research is quantitative research with purposive sampling technique. The population of this study is manufacturing companies in the various industrial sectors listed on the Indonesia Stock Exchange in 2019-2021 with a sample of 27 companies. The statistical data analysis method used is panel data regression. The conclusion of this study is that financial stability and effectiveness of supervision have a positive effect on fraudulent financial reporting, while external pressure and financial targets have a negative effect on fraudulent financial reporting.